The Strategic Environment Analysis of Islami Bank Bangladesh Limited (IBBL) - Khan, Md. Rahat; Hossain, S. M. Khaled; Rabbi, Md. Mohaiminul Islam (IIUM Journal of Case Studies in Management, 2018)
Strategic environment analysis is an integral part of any business to create and sustain a competitive position in competitive business arena. IBBL is one of the leading and the pioneer of Islamic banking in Bangladesh. This study focuses on the IBBL’s both the internal & external environment and competitive position. Some very common environmental analyzing tools such as strengths (S), weaknesses (W), opportunities (O), and threats (T), value chain analysis (VCA), resource based view (RBV) analysis, political (P), economic (E), social (S), technological (T), and ecological (E), BCG matrix, along with five competitive forces analysis are used to observe the competitive position of IBBL in Banking industry. The study describes all the analysis after analyzing the IBBL’s business environment under Savar zone.